Molecular characteristics and antibiotic resistance mechanisms of clindamycin-resistant Streptococcus agalactiae isolates in China - Liu, Zeliang; Jiang, Xueqi; Li, Jie; Ji, Wenjing; Zhou, Haijian; Gong, Xinyi; Miao, Beibei; Meng, Shuang; Duan, Like; Shi, Qiyuan; Han, Xiao; Gao, Pengfang; et al. (Frontiers in Microbiology, 2023)
Streptococcus agalactiae (Group B Streptococcus, GBS) is a major cause of neonatal infections with high morbidity and mortality. Clindamycin is the main antibiotic used to treat GBS infections in patients allergic to penicillin. We aimed to analyse the antibiotic sensitivity, sequence types, serotypes, virulence factors, and antibiotic resistance mechanisms of clinically isolated clindamycin-resistant S. agalactiae and provide basic data for the treatment, prevention, and control of clinical infection of S. agalactiae. A total of 110 strains of clindamycin-resistant S. agalactiae were collected from two tertiary hospitals in Hebei, China. We performed antibiotic sensitivity tests for 11 antibiotics on these strains and whole-genome sequencing analysis. All the strains were susceptible to penicillin, ampicillin, linezolid, vancomycin, tigecycline, and quinupristin-dalfopristin. Resistance to erythromycin, levofloxacin, tetracycline, and chloramphenicol were also observed. Genome sequence analysis revealed that all strains belonged to 12 sequence types (STs) related to six cloning complexes (CCs), namely CC10, CC19, CC23, CC651, CC1, and CC17. Five serotypes were identified, including IA, IB, II, III, and V. The most prominent resistance genes were mreA (99.0%) and ermB (91.8%). Furthermore, cfb, cylE, pavA and the gene cluster related to the pili were 100% present in all strains, followed by lmb (95.4%) and srr1 (77.2%). This study found that clindamycin-resistant S. agalactiae showed polymorphisms in molecular types and serotypes. Furthermore, multiple virulence factor genes have been identified in their genomes.